2019
DOI: 10.1101/730036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human cerebrospinal fluid induces neuronal excitability changes in resected human neocortical and hippocampal brain slices

Abstract: Human cerebrospinal fluid (hCSF) have proven advantageous over conventional medium when culturing both rodent and human brain tissue. Increased excitability and synchronicity, similar to the active state exclusively recorded in vivo, reported in rodent slice and cell-cultures with hCSF as recording medium, indicates properties of the hCSF not matched by the artificial cerebrospinal fluid (aCSF) commonly used for electrophysiological recording. To evaluate the possible importance of using hCSF as electrophysiol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In previous studies, we and others showed that hCSF is superior to artificial cerebrospinal fluid and neurobasalbased cultivation medium in promoting electrophysiological function of in vitro neurons in primary neuronal cultures (Perez-Alcazar et al, 2016), murine embryonic stem cell cultures (Otto et al, 2009), rodent brain slices (Bjorefeldt et al, 2015(Bjorefeldt et al, , 2016, and human brain slices (Schwarz et al, 2017;Wickham et al, 2020). However, the morpho-logical and functional supportive impact of hCSF in hiPSCderived 3D neural in vitro models was unknown.…”
Section: Implications For Hipsc-based Neural Development and Neuronal Circuits In In Vitro Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we and others showed that hCSF is superior to artificial cerebrospinal fluid and neurobasalbased cultivation medium in promoting electrophysiological function of in vitro neurons in primary neuronal cultures (Perez-Alcazar et al, 2016), murine embryonic stem cell cultures (Otto et al, 2009), rodent brain slices (Bjorefeldt et al, 2015(Bjorefeldt et al, , 2016, and human brain slices (Schwarz et al, 2017;Wickham et al, 2020). However, the morpho-logical and functional supportive impact of hCSF in hiPSCderived 3D neural in vitro models was unknown.…”
Section: Implications For Hipsc-based Neural Development and Neuronal Circuits In In Vitro Modelsmentioning
confidence: 99%
“…A limitation of all previous work, including ours, is the application of hCSF obtained from unhealthy individuals. For instance, pooled CSF samples obtained from hydrocephalus patients were used as ''control'' CSF in all previous works (Buddensiek et al, 2009(Buddensiek et al, , 2010Gortz et al, 2013;Jantzen et al, 2013;Koch et al, 2019;Otto et al, 2009;Schwarz et al, 2017;Wickham et al, 2020). It has been known for decades that the chemical composition of hydrocephalus CSF differs from healthy CSF (e.g., Del Bigio, 1989), which indicates that these CSF samples might not be suitable to create a healthy, adult brain-like milieu in vitro.…”
Section: Implications For Hipsc-based Neural Development and Neuronal Circuits In In Vitro Modelsmentioning
confidence: 99%